Potential Asymmetrical Threats from Foreign Fighter Returnees in Indonesia [Potensi Ancaman Asimetris Pada Foreign Fighter Returnees di Indonesia] - Taufik Akbar; Pujo Widodo; Syaiful Anwar (Sekretariat Jenderal DPR RI, 2020)
After the defeat of the Islamic State of Iraq and Syria (ISIS) by the attack of the United States coalition forces in Baghouz, the Foreign FighterS who joined ISIS surrendered and were captured by the Syrian Democratic Force (SDF). It resulted in a wave of returnees of Foreign Fighters, of which among the destinations was Indonesia. The return of Indonesian foreign fighters from Syria will bring potential asymmetric threats to Indonesia, which include the acts of terrorism. The main problem in this regard is the nature of the potential threat posed by these foreign fighter returnees in Indonesia, which the study seeks to analyze using a qualitative method with a phenomenological approach. The data collection was carried out through interviews and document studies, which were then analyzed with Miles, Huberman, and Saldana’s analysis technique in 2014. The study employs the concept of foreign fighters and asymmetrical threats, and results of the research indicate that the potential threat of foreign fighter returnees in Indonesia comes in the ability of military returnees, an increase in international networks, movement of war zones (Darul Harb), lone wolf attack tactics and indoctrination of violent extremism.AbstrakPasca kekalahan Islamic State of Iraq and Syria (ISIS) oleh gempuran pasukan koalisi Amerika Serikat di Baghouz, Foreign Fighter yang tergabung ke dalam ISIS menyerah dan tertangkap oleh pasukan Syria Democratic Force (SDF). Dampaknya ialah muncul gelombang kembalinya (returnees) Foreign Fighter, salah satu tujuannya ialah ke Indonesia. Kembalinya foreign fighter Indonesia dari Suriah akan membawa potensi ancaman asimetris bagi Indonesia seperti aksi teror. Hal tersebut memunculkan pertanyaan bagaimana potensi ancaman yang ditimbulkan dari foreign fighter returnees di Indonesia. Tujuan penelitian ini adalah untuk menganalisis bentuk potensi ancaman pada foreign fighter returnees di Indonesia dengan menggunakan metode penelitian kualitatif dengan pendekatan fenomenologi. Pengumpulan data dilakukan melalui wawancara dan studi dokumen, selanjutnya dianalisa dengan teknik analisis Miles, Huberman dan Saldana tahun 2014. Penelitian ini menggunakan konsep foreign fighter dan ancaman asimetris yang hasil penelitiannya menunjukkan bahwa potensi ancaman foreign fighter returnees di Indonesia ialah kemampuan militer returnees, kekuatan jaringan internasional, perpindahan wilayah perang (darul harb), taktik serangan lone wolf dan indoktrinasi ekstremisme kekerasan.